Clinical Characteristics and Treatment Outcomes of Primary Pulmonary Artery Sarcoma in Korea - Yunkyoung Lee; Hyun Jung Kim; Hee‐Young Yoon; Chang‐Min Choi; Yeon‐Mok Oh; Sang‐Do Lee; Chae‐Man Lim; Woo‐Sung Kim; Younsuck Koh; Jae Seung Lee (2016)
Pulmonary artery sarcomas (PAS) are rare malignant neoplasms. Right heart failure due to tumour location is the main cause of death in PAS patients. The hemodynamic influence of PAS may effect prognosis, but this has not been proven. We aimed to identify the clinical characteristics and prognostic factors of PAS in Korea, their association with pulmonary hypertension (PH). PAS patients treated at the Asan Medical Center between 2000 and 2014 were reviewed. We examined demographic characteristics, diagnostic and treatment modalities. Potential prognostic factors were evaluated by univariate and multivariate analysis. Twenty patients were diagnosed with PAS. Ten patients were male, the median age was 54 years (range, 33-75 years). The most common symptom observed was dyspnea (65%). The most common histologic type was spindle cell sarcoma (30%). Ten patients had a presumptive diagnosis of pulmonary embolism (PE) and received anticoagulation therapy. Seventeen patients underwent surgery, but only 5 patients had complete resection. Eleven patients received post-operative treatment (chemotherapy = 3, radiotherapy = 5, chemoradiotherapy = 3). PH was observed in 12 patients before treatment and in 6 patients after treatment. Overall median survival was 24 months. Post-treatment PH was associated with poor prognosis (HR 9.501, 95% CI 1.79-50.32; P = 0.008) while chemotherapy was negatively associated with mortality (HR 0.102, 95% CI 0.013-0.826; P = 0.032) in univariate analysis. Post-treatment PH was also associated with poor prognosis in multivariate analysis (HR 5.7, 95% CI 1.08-30.91; P = 0.041). PAS patients are frequently misdiagnosed with PE in Korea. Post-treatment PH is associated with a poor prognosis.